Circulating tumour DNA methylation in hepatocellular carcinoma diagnosis using digital droplet PCR. Issue 3 (March 2021) - Wang, Juan; Yang, Liu; Diao, Yanjun; Liu, Jiayun; Li, Jinjie; Li, Rui; Zheng, Lianghong; Zhang, Kang; Ma, Yueyun; Hao, Xiaoke
Objective: To evaluate the performance of a DNA methylation-based digital droplet polymerase chain reaction (ddPCR) assay to detect aberrant DNA methylation in cell-free DNA (cfDNA) and to determine its application in the detection of hepatocellular carcinoma (HCC). Methods: The present study recruited patients with liver-related diseases and healthy control subjects. Blood samples were used for the extraction of cfDNA, which was then bisulfite converted and the extent of DNA methylation quantified using a ddPCR platform. Results: A total of 97 patients with HCC, 80 healthy control subjects and 46 patients with chronic hepatitis B/C virus infection were enrolled in the study. The level of cfDNA in the HCC group was significantly higher than that in the healthy control group. For the detection of HCC, based on a cut-off value of 15.7% for the cfDNA methylation ratio, the sensitivity and specificity were 78.57% and 89.38%, respectively. The diagnostic accuracy was 85.27%, the positive predictive value was 81.91% and the negative predictive value was 87.20%. The positive likelihood ratio of 15.7% in HCC diagnosis was 7.40, while the negative likelihood ratio was 0.24. Conclusions: A sensitive methylation-based assay might serve as a liquid biopsy test for diagnosing HCC.